Internalization Model of Hindu Teaching Values in Informal Education - Suta Adnyana, Putu; Jatiyasa, I Wayan (Jayapangus Press, 2023)
The Hindu community is one of the rural communities with a high commitment to maintaining its diversity intact as it is inherited. It can be seen from the implementation of worship that used several facilities such as flowers, incense sticks, water, bija (grain of rice), and others. However, the meaning of its facilities sometimes is not clearly understood. Therefore, examining the Internalization of Hindu Teaching Values in Informal Education is necessary to increase the religious value of the younger generation of Hindus. This study entitled Internalization Model of Hindu Teaching Values in Informal Education raises three issues, including how the internalization process of Hindu teaching values in informal education is, how the form of internalization of Hindu teaching values is, and the implication of the internalization of Hindu teaching values in formal education on children’s behavior. The general objective of this research is to enhance thinking in developing science. In addition, it aimed to examine the related processes with the internalization model of Hindu teaching values in informal education. This research is qualitative research using descriptive data analysis. Informants were determined purposively. The data were collected using the observation, interviews, and documentation methods. It was analyzed in several stages: data reduction, data presentation, and conclusion. The results of this study obtained 1) The internalization process of Hindu teaching values was divided into two, namely: (a) Children imitated their parents’ behavior in performing religious rituals; (b) The children observed religious procedures following the religious ceremonies. 2) Forms of internalized Hindu values ​​were: (a) Parents taught the implementation of the ceremony in accordance with what has been passed down; (b) Parents familiarized their children to differentiate how to speak and dress nicely; (c) Parents accustomed their children to pray every day. 3) Implications of the internalization of Hindu teaching values were: (a) making children afraid to violate cultural heritage; (b) making children have the ethics of speaking and dressing nicely; (c) making the child perform a steady religious ceremony.